Safety and tolerability of moxidectin and ivermectin combination treatments for lymphatic filariasis in Côte d'Ivoire: A randomized controlled superiority study. - Catherine M Bjerum; Benjamin G Koudou; Allassane F Ouattara; Daphne Lew; Charles W Goss; Pascal T Gabo; Christopher L King; Peter U Fischer; Gary J Weil; Philip J Budge (Public Library of Science (PLoS), 2023)
Background Moxidectin is a macrocyclic lactone registered for the treatment of human onchocerciasis. The drug has a good safety profile, large volume of distribution and a long elimination half-life. This paper reports tolerability data from the first use of moxidectin in persons with Wuchereria bancrofti infection. Methods In this randomized, open-label, masked-observer superiority trial, adults with Wuchereria bancrofti microfilaremia in Côte d'Ivoire were randomized to 1 of 4 treatment arms: ivermectin + albendazole (IA), moxidectin + albendazole (MoxA), ivermectin + diethylcarbamazine (DEC) + albendazole (IDA), or moxidectin + DEC + albendazole (MoxDA). As part of a larger efficacy trial, all participants were closely monitored for 7 days after treatment. Results One hundred sixty-four individuals were treated, and monitored for treatment emergent adverse events (TEAE). Eighty-seven participants (53%) experienced one or more mild (grade 1) or moderate (grade 2) TEAE. Four participants had transient Grade 3 hematuria after treatment (3 after IDA and 1 after IA). There were no serious adverse events. There were no significant differences in frequency or types of TEAE between treatment groups (IA = 22/41 (53%), MoxA = 24/40 (60%), IDA = 18/41 (44%), MoxDA = 15/42 (36%), p = 0.530). Fifty-nine participants (36%) had multiple TEAE, and 8.5% had a one or more grade 2 (moderate) TEAE. Grade 2 TEAE were more frequent after triple drug treatments (IDA, 14.6%; MoxDA, 9.5%) than after two-drug treatments (IA, 7.3%; MoxA, 2.5%). There was no difference in TEAEs based on baseline Mf counts (OR 0.69 (0.33, 1.43), p-value 0.319). Conclusion All treatment regimens were well tolerated. We observed no difference in safety parameters between regimens that contained ivermectin or moxidectin. Trial registration Clinicaltrials.gov, NCT04410406.